Polycystin-1 Downregulation Induced Vascular Smooth Muscle Cells Phenotypic Alteration and Extracellular Matrix Remodeling in Thoracic Aortic Dissection - Zhang, Jing; Liu, Fei; He, Yu-bin; Zhang, Wei; Ma, Wen-rui; Xing, Jie; Wang, Li-xin (Frontiers in Physiology, 2020)
Objective: polycystin-1 (PC-1) is a protein encoded by the gene of polycystic kidney disease-1 (PKD-1). This study was designed to investigate the regulatory mechanisms of PC-1 on phenotypes of aortic vascular smooth muscle cells (VSMCs) and functions of extracellular matrix (ECM) in thoracic aortic dissection (TAD). Methods: Aortic tissues from patients with TAD and healthy controls were collected, primary aortic VSMCs were also isolated. Immunohistochemistry, immunofluorescence and immunocytochemistry was used to visualize the target proteins. Western blot and RT-qPCR were used to examine the expression of mRNA and proteins. Lentivirus infection was used to downregulate or overexpress PC-1. Results: Compared with the control group, expression of PC-1 and the contractile phenotypic markers of VSMCs were decreased in TAD group, whereas expression of the synthetic markers of VSMCs, matrix metalloproteinase (MMP)-2, collagen I and collagen III were increased. The phosphorylation of mTOR, S6K and S6 were also elevated in TAD group. PC-1 downregulation of aortic VSMCs inhibited the expression of the contractile markers, but elevated the expression of the synthetic markers, MMP-2, collagen I and collagen III compared with the control group. The phosphorylation of mTOR, S6K and S6 were also increased in PKD-1-knockdown VSMCs. PC-1 upregulation reversed all these expression characteristics in aortic VSMCs. Furthermore, rapamycin treatment to PKD-1-knockdown VSMCs inhibited the effects caused by PC-1 downregulation. Conclusions: Our study revealed PC-1 downregulation induces aortic VSMCs phenotypic alteration and ECM remodeling via activation of mTOR/S6K/S6 signaling pathway. Downregulation of PC-1 might be a potential mechanism for the development and progression of TAD. Rapamycin might be a potential inhibitor to attenuate the development and progression of TAD.